An Outline for Serbian Political Tradition in the Work of Slobodan Jovanović - Bazić, Jovan R.; Popović, Ljubiša M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The paper presents considerations of the research on the Serbian political tradition in the work of Slobodan Jovanović (1869-1958), a famous Serbian lawyer, historian, writer and politician, who had a very important role in the development of the Serbian political thought. His work is extensive and varied, but in essence, it relates to the whole of political life in Serbia in the second half of the nineteenth and the first half of the twentieth century. Almost all the elements that make up the Serbian political tradition can be observed in his work.All these elements are contained in the discussion of political institutions in the 19th century Serbia, the rule of the Obrenović dynasty, political parties and party leaders, political ideas and movements in Serbia and Yugoslavia, extreme political behavior and Serbian national character. Jovanović found the origins of Serbian political tradition in the epic poetry and the Kosovo myth, as well as in the poetry of Njegoš. This was a decisive factor in the formation of general ideas about the Serbs as a freedom-loving, heroic and justice-loving people. At the same time, this is where the origins of the idea of Serbs as a disunited nation can be found. Jovanović paid the greatest attention to issues concerning the content of Serbian political tradition, namely: constitutional system, political institutions, parliamentary life, inter-party struggles, political events, the the role of the individual in politics and culture, authoritarianism and political violence.He pointed to the political ideas that were coming from the West and which were accepted with mistrust by the patriarchal Serbian society. He appreciated the role of political parties in the democratization of political life, but he also warned of the dangers that threatened national unity: party favouritism and intolerance. In the analyses of the Serbian national character, Jovanović was of the opinion that the Serbs are predominantly a "Dinaric type" people, which is characterised by the highly developed sense of justice but not of legality, because it was difficult for them to get accustomed to the laws and could not rid themselves of the biasin favour of relatives and friends in their public life.Regarding Yugoslavism, Jovanovic was its critic, but he pointed out to therational reasons for the unification of Serbs and Croats, which could be established on a compromise of Serbian and Croatian nationalism. He particularly devoted his attention to the Serbian cultural pattern and indicated that, in its absence, it often came to the corruption in public life, which was most noticeable in politics. That is why he advocated the formation of a humanistic cultural pattern, which would be directed to the development of people and would cover the whole of the spiritual life. The work of Slobodan Jovanović expressed a very critical approach to many issues of Serbian political tradition, but it also expressed very clear Enlightenment appeals for the necessity of humanistic education for the development of democratic political culture in Serbia.